A physiology‐based trigger score to guide perioperative transfusion of allogeneic red blood cells: A multicentre randomised controlled trial. Issue 5 (24th May 2022) - Lu, Kejian; Huang, Zehan; Liang, Shucong; Pan, Fengting; Zhang, Chunying; Wei, Jingqing; Wei, Huijun; Wang, Yafeng; Liao, Ren; Huang, Ailan; Huang, Yanjuan
Abstract: Background: Restrictive blood transfusion is recommended by major guidelines for perioperative management, but requires objective assessment at 7–10 g/dl haemoglobin (Hb). A scoring system that considers the physiological needs of the heart may simply the practice and reduce transfusion. Methods: Patients (14–65 years of age) undergoing non‐cardiac surgery were randomised at a 1:1 ratio to a control group versus a Perioperative Transfusion Trigger Score (POTTS) group. POTTS (maximum of 10) was calculated as 6 plus the following: adrenaline infusion rate (0 for no infusion, 1 for ≤0.05 μg·kg −1 ·min −1, and 2 for higher rate), FiO2 to keep SpO2 at ≥95% (0 for ≤35%, 1 for 36%–50%, and 2 for higher), core temperature (0 for <38°C, 1 for 38–40°C, and 2 for higher), and angina history (0 for no, 1 for exertional, and 2 for resting). Transfusion is indicated when actual Hb is lower than the calculated POTTS in individual patients. Transfusion in the control group was based on the 2012 American Association for Blood Banks (AABB) guideline. The primary outcome was the proportion of the patients requiring transfusion of allogeneic red blood cells (RBCs) during the perioperative period (until discharge from hospital), as assessed in the intention‐to‐treat (ITT) population (all randomised subjects). Result: A total of 864 patients (mean age 44.4 years, 244 men and 620 women) were enrolled from December 2017 to January 2021 (433 in the control and 431 in the POTTS group). Baseline Hb was 9.2 ± 1.8 and 9.2 ± 1.7 g/dl in the control and POTTS groups, respectively. In the ITT analysis, the proportion of the patients receiving allogeneic RBCs was 43.9% (190/433) in the control group versus 36.9% (159/431) in the POTTS group ( p = 0.036). Lower rate of allogeneic RBCs transfusion in the POTTS group was also evident in the per‐protocol analysis (42.8% vs. 35.5%, p = 0.030). Transfusion volume was 4.0 (2.0, 6.0) and 3.5 (2.0, 5.5) units (200 ml/unit) in the control and POTTS groups, respectively ( p = 0.25). The rate of severe postoperative complications (Clavien‐Dindo grade IIIa and higher) was 3.9% in the control group versus 1.2% in the POTTS group ( p = 0.010). Conclusion: Transfusion of allogeneic RBCs based on the POTTS was safe and reduced the transfusion requirement in patients undergoing non‐cardiac surgery.